Semiotics in the song Saat Kau Telah Mengerti by Virgoun - Widhiarto, Annisa Karunia; Illona, Fatiha; Suryaningrum, Dewi; Hapsari, Anggalia Tri; Muzaki, Helmi; Zunoomy, Muhammadu Sainulabdeen; Bello, Idris Muhammad (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to describe the connotation and denotation meanings in the song entitled Saat Kau Telah Mengerti (When You Understand) by Virgoun. In this article, the method used descriptive qualitative and analyses using Roland Barthes' semiotic theory, which discusses the concepts of denotation and connotation. According to Barthes' concept, a denotative sign consists of a signifier and a signified, but it also functions as a connotative sign. This means that the connotative sign not only has an additional meaning, but also consists of both parts of the denotative sign on which it is based. The results of this study reveal that there are ten song lyrics that contain denotative meaning and sixteen song lyrics that contain connotative meaning. The song Saat Kau Telah Mengerti has a meaning in the form of messages and hopes of parents to children. In its song, the songwriter as a parent wants to give the best for his child. However, action taken by parents for their children’s benefit can occasionally cause the child to feel upset or angry.